Gaya Komunikasi Kepala Madrasah dalam Meningkatkan Kinerja Guru di Yayasan Nururrodhiyah Kota Jambi - Muh. Mintari; Fadlilah Fadlilah; Bawaihi Bawaihi (Management of Islamic Education Department, Faculty of Education and Teacher Training, State Islamic University Sulthan Thaha Saifuddin Jambi, 2020)
This study aims to describe the communication style of madrasah heads in improving teacher performance at yayasan Nururrodhiyah Jambi City. This study uses qualitative methods. Data collection techniques using observations, interviews, and documentation. The results of the study found there are two communication styles of madrasah heads at nururrodhiyah foundation in improving teacher performance, first, the equalitarian style; give teachers the opportunity to express suggestions or opinions. Second, the relinguishing style; reflects the willingness to accept the suggestions, opinions or ideas of others, rather than the wishes of the command, even though the head of the madrasa has the right to give orders.